Spatio-Temporal Control of Cell Adhesion: Toward Programmable Platforms to Manipulate Cell Functions and Fate - Cimmino, Chiara; Rossano, Lucia; Netti, Paolo Antonio; Ventre, Maurizio (Frontiers in Bioengineering and Biotechnology, 2018)
Biophysical and biochemical signals of material surfaces potently regulate cell functions and fate. In particular, micro- and nano-scale patterns of adhesion signals can finely elicit and affect a plethora of signalling pathways ultimately affecting gene expression, in a process known as mechanotransduction. Our fundamental understanding of cell-material signals interaction and reaction is based on static culturing platforms, i.e. substrates exhibiting signals whose configuration is time-invariant. However, cells in vivo are exposed to arrays of biophysical and biochemical signals that change in time and space and the way cells integrate these might eventually dictate their behaviour. Advancements in fabrication technologies and materials engineering, have recently enabled the development of culturing platforms able to display patterns of biochemical and biophysical signals whose features change in time and space in response to external stimuli and according to selected programmes. These dynamic devices proved to be particularly helpful in shedding light on how cells adapt to a dynamic microenvironment or integrate spatiotemporal variations of signals. In this work, we present the most relevant findings in the context of dynamic platforms for controlling cell functions and fate in vitro. We place emphasis on the technological aspects concerning the fabrication of platforms displaying micro- and nano-scale dynamic signals and on the physical-chemical stimuli necessary to actuate the spatiotemporal changes of the signal patterns. In particular, we illustrate strategies to encode material surfaces with dynamic ligands and patterns thereof, topographic relieves and mechanical properties. Additionally, we present the most effective, yet cytocompatible methods to actuate the spatio-temporal changes of the signals. We focus on cell reaction and response to dynamic changes of signal presentation. Finally, potential applications of this new generation of culturing systems for in vitro and in vivo applications, including regenerative medicine and cell conditioning are presented.